The role of 2-ethylhexanoic acid in manipulating the morphology and upconversion of flame-made Y2O3:Yb3+/Ho3+ nanoparticles towards remote temperature sensing. Issue 39 (22nd September 2022) - Hu, Shuai; Yuan, Maohui; Song, Changqing; Han, Kai; Wang, Linxuan; Huang, Hanchang; Cui, Wenda; Yang, Zining; Wang, Hongyan
Abstract : In the flame spray pyrolysis process, 2-ethylhexanoic acid manipulates morphology of Yb 3+ /Ho 3+ co-doped Y2 O3 upconversion nanoparticles towards homogeneous and ultrafine but causing upconversion luminescence quenching and thermal sensitivity lowering. Abstract : Flame spray pyrolysis (FSP) is a potential strategy to scale-up the fabrication of upconversion nanoparticles (UCNPs) from the laboratory to industrial-scale production. The traditional FSP method involves the addition of 2-ethylhexanoic acid (2-EHA) to the precursors to obtain pure homogeneous ultrafine nanoparticles. However, there is still a lack of investigation into how the physical and optical properties are affected by 2-EHA. Here, for the first time, we report the role of 2-EHA in manipulating the morphology, size, and upconversion (UC) properties of Yb 3+ /Ho 3+ co-doped Y2 O3 UCNPs. The Y2 O3 :Yb 3+ /Ho 3+ UCNPs were synthesized by adjusting the molar ratios of 2-EHA to trivalent rare earth ions (RE 3+ ) in the precursor solution via the FSP method. The influence on the morphology and upconversion luminescence (UCL) properties of the UCNPs by 2-EHA was studied in detail. As the ratio of 2-EHA to RE 3+ (2-EHA/RE 3+ ) in the precursors increases from 0 to 3, the synthesized UCNPs initially form a mixture of large hollow particles and homogeneous ultrafine nanoparticles at low ratios and then uniform ultrafine nanoparticles at relatively high ratios. The typical green (550 nm) and red (667 nm) UCL reduce as the 2-EHA/RE 3+ ratio increases. Moreover, the effect of 2-EHA on the temperature sensing behavior of the Y2 O3 :Yb 3+ /Ho 3+ UCNPs was evaluated via the fluorescence intensity ratio (FIR) method based on the non-thermally coupled 5 F4 / 5 S2 and 5 F5 levels of Ho 3+ ions. The highest absolute sensitivity ( S A ) and relative sensitivity ( S R ) of 6.259% and 0.483% K −1 at 323 K, respectively, were determined and the sensitivity dependence on the 2-EHA/RE 3+ ratio of the UCNPs was comparatively estimated.